IMPLEMENTASI PENGELOLAAN DANA DESA DALAM MENINGKATKAN TARAF HIDUP MASYARAKAT DI DESA GUNUNG SALAK KECAMATAN SELEMADEG TIMUR KABUPATEN TABANAN - I Ketut Suardana (Locus, 2022)
This study aims to determine the implementation of village fund management in improving the living standards of the community in Gunung Salak Village, East Selemadeg District, Tabanan Regency. The subject of this study was the implementation of village fund management in improving the living standards of the community in Gunung Salak Village, East Selemadeg District, Tabanan Regency.  Data were collected by observation techniques, interview techniques and documentation techniques and the data were analyzed in a simple way using qualitative descriptive methods.  The results showed that the :(1) Implementation / implementation of Village Fund Management in Gunung Salak Village, East Selemadeg District, Tabanan Regency has been implemented based on government regulations and the budget has been adjusted to the APBDes that has been compiled by the Village Government,(2) The implementation of Village Fund Management from the State Budget is carried out in village development activities and community empowerment activities so that it has a good impact on improving the standard of living of the people of Gunung Salak Village. (3) The general management obstacle is that project work is very dependent on weather, especially village development projects such as road procurement/repair. (4) The positive impact of village fund management is that it can advance the economy in the village which is directly felt by all levels of society, and the negative impact is that there is a lot of social jealousy, especially between village groups, because the amount of assistance provided is different according to the productivity of the group.